2013
DOI: 10.1128/aac.01069-13
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the ompK36 Porin Gene and Promoter Impact Responses of Sequence Type 258, KPC-2-Producing Klebsiella pneumoniae Strains to Doripenem and Doripenem-Colistin

Abstract: d Doripenem-colistin exerts synergy against some, but not all, Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae strains in vitro. We determined if doripenem MICs and/or ompK36 porin gene mutations impacted the responses of 23 sequence type 258 (ST258), KPC-2-producing strains to the combination of doripenem (8 g/ml) and colistin (2 g/ml) during time-kill assays. The median doripenem and colistin MICs were 32 and 4 g/ml. Doripenem MICs did not correlate with KPC-2 expression levels. Five and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 43 publications
8
88
0
Order By: Relevance
“…Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29). Recent studies from our group and others have demonstrated striking diversity in the core genome of ST258 K. pneumoniae strains, including strains recovered from patients at single centers or longitudinally from the bloodstreams of individual patients (26,28).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29). Recent studies from our group and others have demonstrated striking diversity in the core genome of ST258 K. pneumoniae strains, including strains recovered from patients at single centers or longitudinally from the bloodstreams of individual patients (26,28).…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, ST258 strains were distinct by genotypes (presence of particular molecular mechanisms of antimicrobial resistance) and/or phenotypes (antimicrobial susceptibility profiles). Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nutrients and other hydrophilic molecules, such as ␤-lactam antibiotics, diffuse through these channels, and changes in these pores are linked to decreases in ␤-lactam susceptibility (7-9, 37-39). Previously described changes include disruption of the porin gene or promoter by insertion sequences (IS), frameshifts, nonsense mutations, and insertions or duplications that increase electronegativity of the inner channel-exposed loop 3 region of OmpK porins (40)(41)(42)(43)(44)(45).…”
Section: Detection Of Genes Encoding ␤-Lactamases and Plasmid Typingmentioning
confidence: 99%